Estudio de la densificación de materiales tratados con ligantes hidráulicos bajo vibración horizontal - Reyes, Fredy; Molina, María Teresa; Valencia, Sandra (Revista de Ingeniería, 1999)
The study of vibrating effects over treated materials has developed a characterisation of optimum ranges in which every mix can reach specified density effects. The analysis made of these types of mixes shows the reological behaviour under amplitude and frequency variations a few seconds after the application of the given parameters. However, after applying these parameters, the gained compactness is almost zero. El uso de medios distintos de aplicación de la vibración por ejemplo, utilizando vibración horizontal, puede alcanzar mejores resultados que si es aplicada en superficie como usualmente lo hacen los compactadores.